2002
DOI: 10.1002/jcop.10036
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Boys and Girls Clubs and relationships to youth outcomes

Abstract: Ⅲ Participation is a key issue in youth development organizations. In fact, research suggests that youths who attend the programs offered by these agencies will experience numerous benefits. One such youth development organization is the Boys and Girls Clubs of America (BGCA). A R T I C L E JOURNAL OF COMMUNITY PSYCHOLOGY, Vol. 31, No. 1, 39-55 (2003) © 2003 Wiley Periodicals, Inc. Published online in Wiley InterScience (www.interscience.wiley.com). DOI: 10.1002/jcop.10036 Youth development programs provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 23 publications
2
39
2
Order By: Relevance
“…In educational socialization of the children's association the researchers (Anderson-Butcher, Newsome, Ferrari, 2003;Akiva, Cortina, Jacquelynne, Eccles, Smith, 2013;Peterson, et al, 2011) visualize the possibility and the necessity "to see the child as he is", understand his needs and interests in the natural environment of activities of the children community (and not through some artificial tests, quests, trainings), shape and develop this community taking into account the data on the actual children (Selivanova, & Belyaev, 2014;Anderson-Butcher, Newsome, Ferrari, 2003;Blanchet-Cohen, Brunson, 2014;Peterson, et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In educational socialization of the children's association the researchers (Anderson-Butcher, Newsome, Ferrari, 2003;Akiva, Cortina, Jacquelynne, Eccles, Smith, 2013;Peterson, et al, 2011) visualize the possibility and the necessity "to see the child as he is", understand his needs and interests in the natural environment of activities of the children community (and not through some artificial tests, quests, trainings), shape and develop this community taking into account the data on the actual children (Selivanova, & Belyaev, 2014;Anderson-Butcher, Newsome, Ferrari, 2003;Blanchet-Cohen, Brunson, 2014;Peterson, et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Even proactive educators being faced the difficult start-up phase, stop their activities and it is difficult to reproach them. Lack of support, understanding, business cooperation and interaction leads to the fact that a large part of children public associations at an early stage of their existence cease to function or turn into further education associations and associations of the club type (Kruglov, 2014;Anderson-Butcher, Newsome, Ferrari, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Anderson-Butcher et al (2003) found that simply attending a Boys and Girls Club was associated with increased academic achievement and lower levels of truancy. Additionally, they found that club attendance buffered the typical developmental increase in favorable attitudes toward cheating in school and alcohol use associated with increasing age.…”
Section: Youth Program Attendancementioning
confidence: 96%
“…Thus, more research examining the impact of program attendance on internalizing symptomatology is needed, as understanding the impact of program attendance on depressive symptoms could be helpful in refining current prevention and intervention efforts for child depression. Based on the literature suggesting that youth programs are helpful in reducing negative behavior and improving academic achievement (e.g., Anderson-Butcher et al, 2003), higher levels of program attendance were expected to be associated with lower levels of depressive symptoms. Furthermore, just as attending these programs has been found to buffer the impact of age-related effects of attitudes toward cheating in school and alcohol use (Anderson-Butcher et al), high levels of program attendance were expected to buffer the impact of neighborhood problems on child depressive symptoms.…”
Section: Youth Program Attendancementioning
confidence: 99%
“…As such, the current study begins to explore the content of weblog postings through a risk and resilience framework. This approach is useful for examining the content of blog postings among adolescents, especially as it provides a theory-driven perspective related to how specific experiences or conditions relate to positive youth development (Anderson-Butcher et al 2003;Fraser 2004;Fraser et al 1999;Guerra and Bradshaw 2008;Hawkins et al 1992;Jensen and Fraser 2006).…”
Section: The Current Studymentioning
confidence: 98%